ANALISIS BILANGAN TERHUBUNG PELANGI PADA GRAF PAN - Mahmud, Rauman (Amalgamasi: Journal of Mathematics and Applications, 2025)
This study discusses the rainbow connection number of pan graphs. The concept of rainbow connection is one of the important topics in graph theory related to edge coloring, where a path connecting any pair of vertices must consist of edges with distinct colors. Determining the rainbow connection number is relevant in the fields of network optimization, communication security, and the design of efficient transportation routes. In this research, a structural analysis approach of pan graphs is employed to determine the lower and upper bounds, as well as to obtain the exact value of the rainbow connection number. The results reveal a specific connectivity pattern in pan graphs that affects the minimum number of colors required